Ukuran Perusahaan, Profitabilitas, Dan Leverage Terhadap Islamic Social Reporting Pada Bank Umum Syariah Di Indonesia - Umiyati Umiyati; Muhammad Danis Baiquni (Jurnal Akuntansi dan Keuangan Islam, 2018)
This research discusses the effect of firm size, profitability, and leverage on Islamic Social Reporting (ISR) at Sharia Commercial Bank in Indonesia. The sample is 8 Syariah Commercial Banks in Indonesia within the period from 2011 to 2015. Dependent variable in this research is ISR, using method of content analysis. Firm size is measured by total company asset, profitability is matched by ROA and ROE, as well as leverage is measured by DAR is an independent variable. The method of analysis is multiple linear regression using panel data and processed using Eviews version 9.0. The result shows simultaneously firm size, ROA, ROE, and DAR effect against ISR. That partially only variable of firm size that significant effects to ISR, while ROA, ROE and DAR has no significant effect to ISR